DEVELOPMENT OF ANALYTICAL METHOD FOR SPECTROPHOTOMETRIC DETERMINATION OF BORON IN FOOD PRODUCT - Shalihat, Ayu
Despite an offence against the law, boron as boric acid or borax still might be added to food products. In line with risk analysis principle, the presence of boron in food should be considered as a source of chemical hazard and hence should be identified and determined. The aim of this research was to obtain a spectrophotometric method applicable for determination of boron in food products. Boron was reacted with pyridoxine to form a complex measureable in UV region. Complex formation was observed in pH range of 5,5 to 8,5, in which optimum complex was formed at pH 7 showing wave length with maximum absorbance at 302 nm. Calibration curve in the range of 0 to 5 ppm shows gut linearity with an equation of y = 0,0135x + 0,3715 and a correlation coefficient of 0,99. Absorbance of boron-pyridoxine complex measured at 302 nm was stable up to 60 minutes. The complex formation under influence of interfering metal cations including Pb2+ , Cd2+ , Cu2+ , Al3+ , Zn2+ , Fe3+ and Mg2+ was also observed. For precision and accuracy test, lontong was selected as matrix model due to common boron addition to this food product. The precision of the method, calculated as relative standard deviation (RSD) was 2,349 % while its accuracy, calculated as % of recovery at concentration level of 160, 200 and 240 ppm were 103,78; 113,82 and 100,72 %, respectively. Limit of detection (LOD) and limit of quantification (LOQ) based on statistical method were 0,7652 dan 2,0353 ppm, respectively. Based on overall results, it was concluded that the developed method can be applied for determination of boron in food.